2022
DOI: 10.47068/ctns.2022.v11i22.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spectroscopy in Analysis of Some Floral Honey Samples Collected From Four South Romanian Counties in 2021

Abstract: Honey is a concentrated aqueous solution of sugars, especially glucose and fructose, and minor amounts of dextrin, enzymes, volatile oils, organic acids, ethers, and minerals. Honey samples vary in quality according to various factors, such as climate diversity, geographical characteristics, floral supply period, and packaging and storage conditions, which can compromise the quality of the hive's final product. The assessment of honey quality is a major concern that has gained interest internationally because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Studies carried out on multifloral honey highlight the influence of the type of plant, region, and quality of the environment on total phenol content: values ranging between 23.69-102.16 mg GAE/100 g were found on multifloral honey from Poland [45]; lower results were obtained by Bertoncelj et al, 2007, of 12.68-19.46 mgGAE/100 g on Slovenian multifloral honey [8]. The results of TPC and TFC in our research are lower compared to the results of total phenol content (350.80-565.90 mg GAE/100 g) and of total flavonoid content (29.01-29.48 mg QE/100 g) of multifloral honey from Banat Region of Romania found by Pătruică et al, 2022 [2]; also, increased values were obtained in the study conducted by Giosanu et al, 2022, on multifloral honey samples from the south of Romania (80.19-170.79 mg GAE/100 g and 3.13-19.64 mg QE/100 g) [15]. 4.2.…”
Section: Physicochemical Determinationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies carried out on multifloral honey highlight the influence of the type of plant, region, and quality of the environment on total phenol content: values ranging between 23.69-102.16 mg GAE/100 g were found on multifloral honey from Poland [45]; lower results were obtained by Bertoncelj et al, 2007, of 12.68-19.46 mgGAE/100 g on Slovenian multifloral honey [8]. The results of TPC and TFC in our research are lower compared to the results of total phenol content (350.80-565.90 mg GAE/100 g) and of total flavonoid content (29.01-29.48 mg QE/100 g) of multifloral honey from Banat Region of Romania found by Pătruică et al, 2022 [2]; also, increased values were obtained in the study conducted by Giosanu et al, 2022, on multifloral honey samples from the south of Romania (80.19-170.79 mg GAE/100 g and 3.13-19.64 mg QE/100 g) [15]. 4.2.…”
Section: Physicochemical Determinationsmentioning
confidence: 89%
“…The melissopalynological analysis is usually used to identify the botanical origin and the pollen spectrum to complete the information on the studied honey samples [13,14]. The studies carried out on this food showed that all these characteristics are closely related [15][16][17]. European Union Council Directive 2001/110/EC indicates the maximum allowed levels for some parameters, such as 0.1% for the content of waterinsoluble solids, 0.5% for pressed honey, 20% moisture content, 50 meq kg −1 free acidity, and 0.8 mS cm −1 for electrical conductivity for nectar honey (no less than 0.8 mS cm −1 for chestnut honey).…”
Section: Introductionmentioning
confidence: 99%
“…For the extraction of polyphenols and flavonoids, samples from one gram of crushed and homogenized walnut kernels in 10 mL of ethanol were used and were subjected to the following procedures: vortexing for 5 min at 3000 rpm, ultrasonication for 30 min at 40 kHz, and centrifugation at 6500 rpm for 30 min. The ethanolic extracts were filtered and the determination of the two bioactive compounds was performed immediately after extraction, according to the methodology proposed by Giosanu et al (2018) [50] for the determination of polyphenols and the methodology proposed by Giura et al (2019) [12] for the determination of flavonoids.…”
Section: Extraction Procedures and Biochemical Determinationsmentioning
confidence: 99%
“…An amount of 1 mL filtered extract was used for the determination of these bioactive compounds, according to the methodology proposed by Giosanu et al (2018) [22] (for polyphenols), Giura et al (2019) [23] (for flavonoids and tannins), and Singh et al (2004) [24] (for alkaloids). The content of polyphenols (TPC) and tannins (TTC) was expressed as mg gallic acid equivalents (GAE) 100 g −1 fresh leaves.…”
Section: Extraction Procedures and Biochemical Determinationsmentioning
confidence: 99%